The gain in a chain - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The work-style and the attitudes of many development agencies have become more commercial and business-like in recent years. Where once they focused on handpumps and health, they now also debate the issues of interest rates for small loans, the...